THE ROLE OF NEUROSCIENCE IN MODERN PSYCHOLOGY (Ustozlar uchun, 2025)
This article explores the significant role of neuroscience in modern psychology. The integration of these two fields has provided a deeper understanding of human mental processes, including emotions, memory, learning, and decision-making. Neuroscientific methods such as fMRI, EEG, and PET have enabled the precise study of brain activity, revealing the biological foundations of behavior and cognitive functions. The article also discusses how neuroscience contributes to the understanding and treatment of psychological disorders such as depression, anxiety, and schizophrenia, and how it enhances the effectiveness of psychotherapy through neuroplasticity and evidence-based interventions. Overall, the collaboration between neuroscience and psychology is transforming the field, offering new insights into mental health and therapeutic practices.